Effects of Liming and Phosphorus Fertilization on Growth, Yield and Nutrient Concentration of Papaya (Carica Papaya L.) - Prabhakaran, Raveenranathan (1994)
Two experiments, one ln the field and the other in polybags, were conducted at the MARDI research Station Serdang, to study the effects of four levels of lime and four levels of phosphorus, in factorial combination, on growth, yield and nutrient concentration of papaya cv. Eksotika on a Munchong soil (Tropeptic Hapludox). A randomized complete block design, with two replication sin the field and five in polybags, were used for both the experiments. Uniform seedlings were selected and planted in both trials. For the field experiment, plant height, stem girth and canopy diameter were taken at two month in tervals, soil pH at four month intervals while yield data were recorded from first fruiting until the plants were 1.5 years old. Nutrient concentration was determined on the leaf petiole. The same growth parameters and soil pH were taken at two weekly intervals up to a period of five months from plants in the polybag experiment.